Upper limb manual training for children with cerebral palsy: A systematic review and network meta-analysis of randomized controlled trials. (April 2023) - Yang, Fu-An; Lee, Ting-Hsuan; Huang, Shih-Wei; Liou, Tsan-Hon; Escorpizo, Reuben; Chen, Hung-Chou
Objective: There are different upper limb manual training protocols, namely constraint-induced movement therapy, modified constraint-induced movement therapy, hand–arm bimanual intensive training, hand–arm bimanual intensive training including lower extremity, action observation training, and mirror therapy, available for improving functional outcomes in children with cerebral palsy. However, the effect and priority of these strategies remain unclear. Data sources: We searched the PubMed, Cochrane Library, and Embase databases for relevant articles from inception to October 12, 2022. Review methods: To assess the effect and priority of different strategies of upper limb manual training protocols through a systematic review and network meta-analysis of randomized controlled trials. Results: We included 22 randomized controlled trials in this network meta-analysis. The ranking probability and standard mean differences with 95% credible intervals of the comparison between placebo and other forms of upper limb manual training were as follows: mirror therapy = 2.83 (1.78, 3.88), hand–arm bimanual intensive training including the lower extremity = 0.53 (0.09, 0.96), constraint-induced movement therapy = 0.44 (0.18, 0.71), hand–arm bimanual intensive training = 0.41 (0.15, 0.67), modified constraint-induced movement therapy = 0.39 (0.03, 0.74), and action observation training = 0.18 ( − 0.29, 0.65). No significant inconsistency was noted between the results of direct and indirect comparisons. Conclusion: We suggest that mirror therapy could be the upper limb manual training protocol of choice for improving functional outcomes in patients with cerebral palsy.